Clinical Predictors and Outcome Differences Between Successful and Failed Chronic Total Occlusion Recanalization - Balghith, Mohammed A.; Alharbi, Ibrahim S.; Anezi, Abdurrahman S. Al (Cardiology and Cardiovascular Medicine, 2020)
Background: Coronary artery disease (CAD) remains the number one cause of death worldwide. Chronic total occlusion (CTO) are defined as 100% occlusions with TIMI (Thrombolysis in Myocardial Infarction) 0 flow with at least a 3-month duration, observed in 15-30% of patients undergoing cardiac catheterization. Despite the high incidence of CAD, with the vast majority of patients carrying a high risk factor burden and co-morbidities, there is paucity of data regarding CTO in Saudi Arabia. , It is therefore of extreme importance to understand this challenging type of CAD. Aim: To explore the clinical characteristics and outcome of patients with CTO undergoing cardiac catheterization. Method: We collected data for all adult patients (age > 18 years) with a diagnosis of CTO who underwent coronary angiography at the Cardiac Catheterization Laboratory at King Abdul-Aziz Cardiac Center between January 2010 and December 2017 from electronic databases. We compared clinical characteristics and outcome of patients who underwent successful recanalization versus an unsuccessful outcome. The primary outcome was defined as mortality following the procedure. Secondary outcome was defined as MI, stroke or acute kidney injury as well as CABG required. Results are expressed as mean±SD or median, p<0.05 considered significant. Wilcoxon Rank Sums test for continuous and chi-square for categorical data. Results: In our cohort of 173 patients (mean age 60.2±11.4 years, female 17.9%), the most common risk factors were dyslipidemia (83.2%) and hypertension (76.3%). The most common co-morbidities were heart failure (32.9%) and CKD (12.7%). The most common admitting diagnoses included stable CAD (41.6%), NSTEMI (26%). LAD was the most common location (n=67), followed by RCA (n=63). The Wire was successfully crossed in 72.8 % of cases